THEORETICAL PROVISIONS AND TECHNOLOGY FOR DESIGNING A SAFE PROFESSIONAL AND EDUCATIONAL ENVIRONMENT - A. Kobleva (Вестник Северо-Кавказского федерального университета, 2022)
The article considers the project of technology for step-by-step design of a safe professional and educational environment based on a competence-based approach. The most important objective of development of technology of designing a safe training environment is the creation offavorable conditions for the development of the educational level of the teacher, the growth of level ofprofessional competences, career development, social status, development of his subject position. We believe that the issue ofpreparing a teacher to create a professional educational environment and develop professional competence of a teacher in it is still poorly explored and requires more careful further study.